Isaac N. Phillips, The Revised Ordinances of the City of Bloomington 9 (1876) - (:unkn) unknown (My University, 1876)
Chapter 2. Cemeteries, Section 1. §10. Shooting, Trespassing, etc.--Penalty: Prohibited discharging any firearm, or hunting, or trespassing within the city cemetery or any other cemetery or burying ground within the city. Violators fined not less than ten nor more than one hundred dollars.
Keywords: DISCHARGE; HUNTING REGULATION